EVALUATION OF HEMATOLOGICAL PARAMETERS IN ALBINO RATS EXPOSED DERMALLY TO TANNERY EFFLUENT FROM CHALLAWA INDUSTRIAL ESTATE KANO, NIGERIA. - Bichi, K. A.; Yusif, B. B.; Mustapha, S. B.; Jibrin, Y. U.; Thomas, P. S. (FUDMA JOURNAL OF SCIENCES, 2021)
The effects on haematological parameters of albino rats were evaluated to assess possible toxicity of tannery effluent. The study was carried out for 28 days. Forty (40) matured albino rats of both sexes were divided into four groups of 10 rats each. Group 1 is the control group, which were exposed dermally with normal water. Groups 2, 3 and 4 were exposed dermally at different concentrations of 100%, 50% and 25% of the effluent respectively. The result of the physicochemical analysis of the effluent shows that the physicochemical parameters were above the standard limit. Rats exposed to different percentages of the effluent showed significant decrease in the level of haemoglobin and packed cells volume. Red blood cell, white blood cell, mean corpuscular volume, mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration, platelet and lymphocytes do not significantly decrease or increase.